Antimicrobial activity of psidium cattleianum associated with calcium hydroxide against enterococcus faecalis and candida albicans: An in vitro study - Sangalli, Jorgiana [UNESP]; Jardim Júnior, Elerson Gaetti [UNESP]; Bueno, Carlos Roberto Emerenciano [UNESP]; Jacinto, Rogério de Castilho [UNESP]; Araújo, Gustavo Sivieri de [UNESP]; Gomes Filho, João Eduardo [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Dezan Junior, Eloi [UNESP] (Springer Nature, 2018)
Objective Evaluate, in vitro, the antimicrobial activity of Psidium cattleianum leaf extracts combined with calcium hydroxide against Enterococcus faecalis and Candida albicans biofilm. Materials and methods Dentin specimens obtained from extracted bovine incisors were infected during 14 days with E. faecalis ATCC 29212 and C. albicans ATCC 10231. The specimens were filled with calcium hydroxide pastes prepared with the following vehicles: Psidium cattleianum ethanolic, Psidium cattleianum propylene glycolic, distilled water, and saline as control. After 24 h, 3, 7, and 14 days, the canals were irrigated with sterile saline and dried. Dentin samples were collected from the canals with burs of increasing diameters. To determine the number of colony-forming units (CFU), samples were inoculated onto BHI agar supplemented with yeast extract (0.5%), at 37 °C, for 48 h, in CO2 enriched atmosphere. Comparisons among the groups for the variation factors were performed by ANOVA and Tukey’s test. Results Ethanolic and propylene glycolic extracts showed significantly higher antimicrobial activity against E. faecalis (p <0.01) when compared with distilled water. The ethanolic extract exhibited in 24 h the same antibacterial activity that propylene glycolic extract and distilled water after 7 and 14 days. For C. albicans, all were effective in reducing the number of CFU at all periods. Conclusion The P. cattleianum ethanolic extract presented the fastest and highest antimicrobial activity against E. faecalis, significantly reducing the microbial load in 24 h. All medications were effective against C. albicans. Clinical relevance The antibacterial potential of P. cattleianum and its biological compatibility associated with calcium hydroxide indicate promising applications in the field of dentistry.
Keywords: Calcium hydroxide; Candida albicans; Enterococcus faecalis; Plant extracts